A general strategy to synthesis chitosan oligosaccharide-O-Terpenol derivatives with antibacterial properties. (May 2021) - Yue, Lin; Zheng, Meihong; Wang, Min; Khan, Imran Mahmood; Wang, Bin; Ma, Xiaoyuan; Peng, Chifang; Wang, Zhouping; Xia, Wenshui
Abstract: The objectives of the present study are to synthesize a series of chitosan oligosaccharide-O-Terpenol (COS–O-Ter) derivatives and their implication to evaluate in vitro antibacterial activity. Herein, a general strategy is described for preparing COS–O-Ter derivatives, including substitution and deprotection reactions. The structures of COS–O-Ter derivatives were characterized by FT-IR, 1 H NMR, XRD, TGA, and elemental analysis. COS–O-Ter derivatives revealed the excellent solubility and in vitro antibacterial activity. Moreover, their antibacterial activities were more sensitive to Staphylococcus aureus ( S. aureus ) than Escherichia coli ( E. coli ) indicating the effective potential application of COS–O-Ter derivatives as natural antibacterial agents. The aforementioned study opens a pave to expand the application scope of COS and its derivatives in the food and pharmaceutical industries. Graphical abstract: Image 1 Highlights: Chitosan oligosaccharide derivatives containing terpenol moieties were synthesized. The structure of COS–O-Ter derivatives was confirmed by FT-IR, 1 H NMR, and elemental analysis. The derivatives showed higher antibacterial properties compared to chitosan oligosaccharide.